A Rotational Flap Combined With a Mucosal Advancement Flap for the Lip Reconstruction. Issue 7 (October 2019) - Kim, Jeenam; Lee, Yunhae; Choi, Hyungon
Abstract : Abstract: The lips play an important role in both esthetics and oral functions, so it should be reconstructed in the light of both. The authors present a patient with the upper lateral lip defect after widely excising the basal cell carcinoma. The lip reconstruction was completed with a rotational flap combined with a mucosal advancement flap. By using 2 flaps simultaneously, the defect was covered with sufficient adjacent tissue without severe deformity and tension. At 2-month follow-up, the patient retained good aesthetic results as the scar was on the natural lines of the face. There was no noticeable deformity on the vermilion contour and oral commissure. Oral competence was also good.